2004
DOI: 10.1016/j.tetasy.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The application of monodentate secondary phosphine oxide ligands in rhodium- and iridium-catalyzed asymmetric hydrogenation

Abstract: The application of monodentate secondary phosphine oxide ligands in rhodium-and iridiumcatalyzed asymmetric hydrogenation Jiang, Xiao-bin; van den Berg, Michel; Minnaard, Adriaan; de Vries, Johannes G.; Feringa, B.L. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…The superiority of the self assembling mono-anionic chelate O−anionic  1 -P(III)−phosph(in)ito ligands over non-assembled phosphane ligands in alkene hydroformylation [34,35,194,195] alkene, ketone and imine hydrogenation [196][197][198] and nitrile hydration [32,33,199] argues in favour of the bidentate coordination mode of the anionic phosph(in)ito/phosphinous acid chelate ligand being maintained during the catalytic process due to the strength of the intramolecular hydrogen bond. Lately, bidentate mono O−anionic  1 -P(III)−phosph(in)ite complexes have been involved in a large number of catalytic transformations [176,177,[200][201][202][203][204][205][206].…”
Section: Prevalent Activities In Catalysismentioning
confidence: 99%
“…The superiority of the self assembling mono-anionic chelate O−anionic  1 -P(III)−phosph(in)ito ligands over non-assembled phosphane ligands in alkene hydroformylation [34,35,194,195] alkene, ketone and imine hydrogenation [196][197][198] and nitrile hydration [32,33,199] argues in favour of the bidentate coordination mode of the anionic phosph(in)ito/phosphinous acid chelate ligand being maintained during the catalytic process due to the strength of the intramolecular hydrogen bond. Lately, bidentate mono O−anionic  1 -P(III)−phosph(in)ite complexes have been involved in a large number of catalytic transformations [176,177,[200][201][202][203][204][205][206].…”
Section: Prevalent Activities In Catalysismentioning
confidence: 99%
“…[34] N-or O-Substituted allyllithium compounds may be formed either by a-deprotonation of an allylamine/allyl alcohol derivative or alternatively by g-deprotonation of an enamine/enol derivative. [23] The corresponding N-aryl-(Z)-enol carbamates 19 were made by the method reported by Feringa et al: [35] the sodium enolates of the ketones 18 were O-acylated by addition of the carbamoyl chloride derivatives of N-methyl aniline or N-methyl-4-chloroaniline (Scheme 9). We had previously shown that asymmetric g-deprotonation of an N-carbamoyl enamine (an N-vinyl urea) with chiral lithium amides generates N-substituted allyllithium compounds enantioselectively.…”
mentioning
confidence: 99%
“…[9] Our continued interest in the metal-catalyzed cycloaddition reactions between alkynes and norbornadiene [10] prompted us to investigate the catalytic behavior of palladium(ii) complexes coordinated by SPOs.…”
mentioning
confidence: 99%